General Patterns, Regional Features and the Concept of Non-Western Democracy - Alexei Dmitrievich Voskressenski (Сравнительная политика, 2015)
The article analyzes the approaches to democratization in the Western and non-Western political systems. The author dwells on the methodology for comparative analysis and the system approach, explains the fundamental differences between Western and non-Western political process, taking into account a wide spectrum of socio-cultural, political, economic and ideological factors. The article also examines the peculiarities of the non-Western political systems, their typology and the formation of the concepts of non-Western democracies.